Profiling the immune epigenome across global cattle breeds - Powell, J.; Talenti, A.; Fisch, A.; Hemmink, Johanneke D.; Paxton, E.; Toye, Philip G.; Santos, I.; Ferreira, B.R.; Connelley, T.K.; Morrison, Liam J.; Prendergast, J.G.D. (Springer, 2023)
Background Understanding the variation between well and poorly adapted cattle breeds to local environments and pathogens is essential for breeding cattle with improved climate and disease-resistant phenotypes. Although considerable progress has been made towards identifying genetic differences between breeds, variation at the epigenetic and chromatin levels remains poorly characterized. Here, we generate, sequence and analyse over 150 libraries at base-pair resolution to explore the dynamics of DNA methylation and chromatin accessibility of the bovine immune system across three distinct cattle lineages.